Yield and characterization of rambutan (Nephelium lappaceum) seed flour. - Bernas, Andrea Danica Pacheco
The aim of this study was to process and assess the yield and quality of rambutan seed flour (RSF) from three rambutan varieties namely Aguilar I, Rongrein, and Maharlika. The proximate composition, anti-nutritional component (saponin), minerals (calcium and potassium), and sensorial properties of the rambutan seed flour were determined. The yield of RSF from A was 61.72%, 61.63% in B and 64.16% in C. The moisture, protein, fat, fiber, ash, and carbohydrates in A were 8.20%, 10.40%, 18.80%, 0.44%, 1.29% and 60.86%, respectively, RSF B had 7.99%, 8.89%, 21.66%, 0.29%, 1.22% and 59.95% respectively and RSF C had 8.33%, 7.42%, 23.96%, 0.28%, 1.02% and 58.99%, respectively. One-way ANOVA at 95% confidence level showed that there were significant differences in all the proximate components among sources except for the moisture (P-value of 0.640) and carbohydrates (P-value at 0.478). The fat content of RSF in the 3 varieties were the highest component followed by protein. The anti-nutritional (saponin) content in RSF significantly differ in A at 5.20%, B at 5.03% and C at 4.32%. The saponin present in RSF samples is neither toxic nor beneficial for human consumption. However, the amount of saponin in RSF contributed to the bitterness of the flour sample. Varying levels of calcium and potassium were present among the 3 sources of RSF. The calcium content of RSF in A was 1019 mg/kg, while B and C contained 1064 mg/kg and 1248 mg/kg, respectively. While the potassium content of RSF from A was 3111 mg/kg, B contained 2770 mg/kg and C with 1825 mg/kg. The amount of these minerals in RSF can help in diet supplementation as RSF A, B and C can provide to 10.19%, 10.64%, and 7.91% of calcium, respectively with an RDI of 1g/day and also provide 8.89%, 7.91%, and 5.21% of potassium, respectively with an RDI of 3.5g/day.